Barriers and enablers for the development and implementation of allied health clinical practice guidelines in South African primary healthcare settings: a qualitative study - J. M. Dizon; K. Grimmer; Q. Louw; S. Machingaidze; H. Parker; H. Pillen (BMC, 2017)
Abstract Background The South African allied health (AH) primary healthcare (PHC) workforce is challenged with the complex rehabilitation needs of escalating patient numbers. The application of evidence-based care using clinical practice guidelines (CPGs) is one way to make efficient and effective use of resources. Although CPGs are common for AH in high-income countries, there is limited understanding of how to do this in low- to middle-income countries. This paper describes barriers and enablers for AH CPG uptake in South African PHC. Methods Semi-structured individual interviews were undertaken with 25 South African AH managers, policymakers, clinicians and academics to explore perspectives on CPGs. Interviews were conducted by researcher dyads, one being familiar with South African AH PHC practice and the other with CPG expertise. Rigour and transparency of data collection was ensured. Interview transcripts were analysed by structuring content into codes, categories and themes. Exemplar quotations were extracted to support themes. Results CPGs were generally perceived to be relevant to assist AH providers to address the challenges of consistently providing evidence-based care in South African PHC settings. CPGs were considered to be tools for managing clinical, social and economic complexities of AH PHC practice, particularly if CPG recommendations were contextusalised. CPG uptake was one way to deal with increasing pressures to make efficient use of scarce financial resources, and to demonstrate professional legitimacy. Themes comprised organisational infrastructures and capacities for CPG uptake, interactions between AH actors and interaction with broader political structures, the nature of AH evidence in CPGs, and effectively implementing CPGs into practice. Conclusion CPGs contextualised to local circumstances offer South African PHC AH services with an efficient vehicle for putting evidence into practice. There are challenges to doing this, related to local barriers such as geography, AH training, workforce availability, scarce resources, an escalating number of patients requiring complex rehabilitation, and local knowledge. Concerted attempts to implement locally relevant CPGs for AH primary care in South Africa are required to improve widespread commitment to evidence-based care, as well as to plan efficient and effective service delivery models.